Desenvolvimentos institucionais recentes no setor de telecomunicaç\~oes no Brasil - Rodrigo Abdalla Filgueiras de Sousa; Nathalia Almeida de Souza; Luis Claudio Kubota (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This article analyzed the evolution of the regulatory system in the telecommunications sector in Brazil, incorporating important events that have been taking place since privatization, but have not been fully evaluated. Following the framework developed by Levy and Spiller (1993, 1994, 1996), the paper examined both governance structure and incentive model of the institutional context. From the evidences presented, it may be inferred that Brazil has a solid governance structure for the regulatory system. The stability of regulatory governance prevailed over political changes caused by government alternation, and this may be one reason of the continuous flow of investments from private parties in the sector since 1998. The incentive model, on the contrary, suffered from increasing tensions from institutions inside the federal administration. Lack of directives and policies for the sector, and absence of coordination between agents formally constituted were the first problem detected. A second issue was the proliferation of new agents in the recent governments, even without legal commandment, implementing divergent policies. As incentive model affects efficiency of the regulatory system, observed instability might be one of the key factors for the low performance of regulatory activities, permitting natural market failures to be more noticeable.
Keywords: L51; L96; 330; regulation; institutions; governance; telecommunications